Formulation, characterization, and evaluation of matrix-type transdermal patches of a model antihypertensive drug - Jamakandi, V G; Mulla, J S; Vinay, B L; Shivakumar, HN (Asian Journal of Pharmaceutics (AJP), 2014)
T he present investigation was aimed to evaluating the possibility of using different polymeric grades of hydroxy propyl methyl cellulose (6cps, 15cps, and K4M) for the development of transdermal drug delivery systems of nicorandil, an antianginal drug. Prepared matrix-type patches were evaluated for their physicochemical characterization followed by in vitro evaluation. Selected formulations were subjected for their ex vivo studies on porcine ear skin.